Fermented Foods as a Modern Nutrition Trend: Health Benefits and Implications for a Healthy Diet - Judijanto, Loso; Tasya, Amalia; Firayani, Firayani (Pt. Anagata Sembagi Education, 2025)
In the last decade, fermented foods have become an important part of modern nutrition trends that emphasize gut health, immune system, and mental balance. Increasing public awareness of healthy lifestyles, coupled with strong media narratives, have driven the popularity of products such as kimchi, kefir, and miso. Fermentation not only increases nutritional value, but also produces probiotics that play a role in maintaining gut microbiota. Research has shown a significant association between fermented food consumption and a reduced risk of chronic diseases, digestive disorders, and mild mental disorders through the gut-brain axis mechanism. However, these benefits are highly dependent on the type and viability of the microorganisms contained, as well as the consistency of consumption. The lack of adequate regulation and education makes consumers vulnerable to commercial claims that are not based on scientific evidence. This study uses a qualitative approach through a literature review to synthesize empirical findings on the benefits and challenges of implementing fermented foods in a healthy diet. The results demonstrate the need for an evidence-based nutrition approach, accompanied by public policies that support the integration of fermented foods in a contextual and sustainable manner. Collaboration between researchers, governments, and communities is needed so that the potential of fermented foods can be optimized in supporting public health and sustainable food systems